2020
DOI: 10.1007/s11912-020-0885-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukaemia in Its Niche: the Bone Marrow Microenvironment in Acute Myeloid Leukaemia

Abstract: # AbstractPurpose of Review Acute myeloid leukaemia (AML) is a heterogeneous malignancy for which treatment options remain suboptimal. It is clear that a greater understanding of the biology of the AML niche will enable new therapeutic strategies to be developed in order to improve treatment outcomes for patients. Recent Findings Recent evidence has highlighted the importance of the bone marrow microenvironment in protecting leukaemia cells, and in particular leukaemic stem cells from chemotherapy-induced cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 83 publications
0
52
0
Order By: Relevance
“…Thus, low ROS contents have been associated with stemness and quiescence [ 13 , 17 , 20 , 23 ] while intermediate ROS levels were found in more differentiated populations and associated to proliferation and differentiation [ 49 ]. The importance of the microenvironment has also been emphasized, not only in the maintenance of normal hematopoiesis homeostasis [ 10 , 50 , 51 ] but also in leukemic development [ 52 ]. In this study, we used a coculture system composed of primary MSCs from healthy donors and AML cells (cell-lines or primary blasts) to model the leukemic niche and dissect molecular pathways reciprocally induced in the field of redox metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, low ROS contents have been associated with stemness and quiescence [ 13 , 17 , 20 , 23 ] while intermediate ROS levels were found in more differentiated populations and associated to proliferation and differentiation [ 49 ]. The importance of the microenvironment has also been emphasized, not only in the maintenance of normal hematopoiesis homeostasis [ 10 , 50 , 51 ] but also in leukemic development [ 52 ]. In this study, we used a coculture system composed of primary MSCs from healthy donors and AML cells (cell-lines or primary blasts) to model the leukemic niche and dissect molecular pathways reciprocally induced in the field of redox metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most AML blasts and especially LSCs acquire CXCR4 expression [44,45]. Moreover, high CXCR4 expression on AML is a negative prognostic factor associated with reduced overall and relapse-free survival [46]. CXCL12, similarly to its multi-functional effects on HSCs, acts as a pleiotropic chemokine also in AML.…”
Section: Cxcl12-cxcr4 Axismentioning
confidence: 99%
“…Mohle et al first reported a role of CXCL12-CXCR4 axis in the regulation of AML cells homing and engraftment in the BM niche [47]. Moreover, CXCL12-CXCR4 contributes to AML chemoresistance, as it keeps leukemic cells in close contact with extracellular matrix components, like the integrin VLA-4 and the hyaluronate receptor CD44 [46], and with stromal cells that constitutively secrete growth-promoting and anti-apoptotic signals [48,49].…”
Section: Cxcl12-cxcr4 Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Leukemogenesis is characterized by uncontrolled clonal proliferation of malignant leukemic cells (blasts) that have lost the ability of proper differentiation at various stages of maturation. Our knowledge today suggests that leukemic blasts transduce the surrounding BMM into a leukemia-supportive niche and vice-versa, pointing at a bidirectional crosstalk between leukemic blasts and BMM reciprocally supporting further disease progression [ 1 ]. In adults, AML represents the most common form of acute leukemia whilst in pediatrics, it accounts for 20% of all childhood leukemias with an overall survival of about 70% that ranges from 60% to 90% depending on the risk profile [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%